Comparative Assessment of the Whole-cell Pertussis Vaccine Potency Using Serological and Intracerebral Mouse Protection Methods - D. Mohammadbagher; M. Noofeli; G. Karimi (Archives of Razi Institute, 2019)
One of the most important QC tests of whole-cell pertussis vaccine (WCPV) is potency test. In this regard, mouse protection test (MPT) is the current potency method, which is associated with severe animal distress and large variability in results. The purpose of this study was to assess Pertussis Serological Potency Test (PSPT) as a serological alternative method to intracerebral challenge in MPT assay. In the current study, the potency of three experimental batches of WCPV (1, 2, and 3) and standard vaccine were compared using MPT and PSPT methods. In the MPT method, mice were immunized with tests and standard vaccines. After 2 weeks, they were intracerebrally challenged with Bordetella pertussis strain (18323). The potency was calculated via parallel line analysis based on the numbers of survivors 2 weeks after the challenge. Similar to MPT method, mice were immunized in the PSPT method and bled after 4 weeks. In the next step, sera were titrated by 18323-WCP-ELISA assay and potency values were estimated via parallel line analysis. Pearson correlation test was used to measure the strength of association between MPT and PSPT assay results. The potency values of the experimental laboratory batches 1, 2, and 3 in MPT assays were 11.14, 5.02, and 4.24 Iu/ml, whereas the obtained results of PSPT assays were 10.32, 4.11, and 3.06 Iu/ml, respectively. The correlation of MPT and PSPT results was 0.807. The findings of the present study demonstrated a significant correlation between MPT and PSPT results. The implementation of PSPT was more advantageous, compared to MPT due to its ethical approaches and less variability in results. The PSPT is a promising alternative method for intracerebral challenge. However, additional validation is needed to support the establishment of this method.